2008
DOI: 10.1371/journal.pone.0002965
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Microarray Studies Reveals a Novel Hematopoietic Progenitor Cell Signature and Demonstrates Feasibility of Inter-Platform Data Integration

Abstract: Microarray-based studies of global gene expression (GE) have resulted in a large amount of data that can be mined for further insights into disease and physiology. Meta-analysis of these data is hampered by technical limitations due to many different platforms, gene annotations and probes used in different studies. We tested the feasibility of conducting a meta-analysis of GE studies to determine a transcriptional signature of hematopoietic progenitor and stem cells. Data from studies that used normal bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…These data were obtained from published studies (20-25, 29), were integrated using Unigene protein IDs, subjected to interarray normalization and then used for analysis. This strategy was shown to be biologically valid strategy for analysis previously by us (30). Our analysis of this integrated dataset demonstrated that the SMAD7, a negative regulator of the TGF-β receptor kinase, was the most significantly differentially expressed gene in MDS and was markedly reduced in most cases (Fig 1, mean log2 expression 8.31 in controls vs 6.32 in mds cases, p <0.0001, Bejmanin Hochberg correction, multiple testing).…”
Section: Resultsmentioning
confidence: 74%
“…These data were obtained from published studies (20-25, 29), were integrated using Unigene protein IDs, subjected to interarray normalization and then used for analysis. This strategy was shown to be biologically valid strategy for analysis previously by us (30). Our analysis of this integrated dataset demonstrated that the SMAD7, a negative regulator of the TGF-β receptor kinase, was the most significantly differentially expressed gene in MDS and was markedly reduced in most cases (Fig 1, mean log2 expression 8.31 in controls vs 6.32 in mds cases, p <0.0001, Bejmanin Hochberg correction, multiple testing).…”
Section: Resultsmentioning
confidence: 74%
“…A number of genes have been identified that are differentially expressed between MDS patients and healthy controls. 32 It is difficult, however, to relate our findings to published microarray data because of the different cellular populations used in different studies. 33,34 Interestingly, deregulated cytokine and innate immune signaling due to interstitial deletion on chromosome 5 in humans and chromosome 11 and 18 in mice has led to the MDS phenotype.…”
Section: Discussionmentioning
confidence: 96%
“…However, this method may cause loss of data due to the removal of all genes whose expression values are missing for any dataset in order to obtain a fully filled data matrix, representing each sample as a column and the values for each gene as a row (for an example of this filtering see [26]). Alternatively, some Authors retain all data values in quantile normalization by placing missing values at the end of each sorted column [27].…”
Section: Discussionmentioning
confidence: 99%